The X linked recessive form of XY gonadal dysgenesis with a high incidence of gonadal germ cell tumours: clinical and genetic studies. Issue 4 (August 1983) - Mann, J R; Corkery, J J; Fisher, H J; Cameron, A H; Mayerová, A; Wolf, U; Kennaugh, A A; Woolley, V
Abstract : Five phenotypic females in one family had the genotype 46, XY and all had gonadal germ cell tumours. Studies of the family pedigree suggest that this form of XY gonadal dysgenesis is inherited in an X linked recessive manner. G banding of elongated metaphase chromosomes from two subjects with XY gonadal dysgenesis and a female carrier showed no aberrations of the X chromosome. The titres of H-Y antigen in three girls with XY gonadal dysgenesis were in the male control range. Thus it appears that, in the X linked form, XY gonadal dysgenesis may be caused by a point deletion or mutation of a gene on the X chromosome, which controls the gonad specific receptor for the H-Y antigen. Studies of Xg blood groups were uninformative about linkage of Xg with the X borne gene causing the XY gonadal dysgenesis. Dermatoglyphic studies in the girls with XY gonadal dysgenesis and female carriers revealed high a-b palmar ridge counts and a tendency for the A mainline to terminate in the thenar area. Both of these features have been described in patients with Turner's syndrome.